Modern Japan : origins of the mind : Japanese traditions and approaches to contemporary life - Prasol, A. F. (Aleksandr Fedorovich), 1952- (World Scientific, 2010)
The book takes a fresh look at modern Japan, and does not treat the Japanese as enigmatic or mysterious people; their ways of thinking and their culture can be explained by an honest appraisal of their history and of the norms that have shaped this history. This book not only reveals the mentality and national character of modern Japanese people but also attempts to explore and analyze the roots of their mannerisms. Everyone knows that the Japanese are generally more polite than other nationalities, but why is this so? Why do they embrace a relaxed attitude when being served by others? Surely, there must be specific reasons to account for these observations. Delving into the social values of the Japanese, why do they value loyalty and commitment so much? How long have they been upholding these virtues? Why, when interrogated by the police, even without being beaten or tortured, do they easily confess guilt for crimes that they have not committed? What are the reasons for such behaviors? All these questions and more are answered in this book.